INTEGRATING NANOTECHNOLOGY CONCEPTS AND ITS APPLICATIONS INTO THE SECONDARY STAGE PHYSICS CURRICULUM IN EGYPT - Selim, Shaimaa Abdul Salam; Al-Tantawi, Ramadan Abdul-Hameed; Al-Zaini, Samia Ahmad (European Scientific Journal, ESJ, 2015)
Nanotechnology is very important in our society. Its concepts pertaining to study the unique characteristics of nano-scale material, which, in turn, helps in producing new materials that can be used in the fields of medicine, industry, engineering, agriculture, drugs, communications, defense, space, among others (Ban & Kocijancic, 2011). In response to the lack of these concepts in the Egyptian secondary school Physics curriculum, the current study aim at integrating some Nanotechnology concepts and applications in this curriculum and seek to answer this question: What â€œnanotechnology concepts and applicationsâ€ should be teach in the secondary school Physics curriculum in Egypt. To do that, the researchers analyzed the content of Physics curricula in some countries and in the three grades of secondary education in Egypt for the school year 2014-2015, and prepared a list of 52 nanotechnology concepts, to be integrated in the secondary-stage Physics curriculum. These concepts were distributed along five basic units (the first unit included 20 concepts, the second unit 11 concepts, the third and fourth units 8 concepts each, and the fifth unit 5 concepts). On the other hand, twenty one concepts of nanotechnology were integrated into the second-grade secondary school Physics curriculum, distributed along three units (Units one and two included nine concepts whereas unit three included three concepts). Regarding the third grade secondary stage Physics curriculum, 17 nanotechnology concepts were integrated and distributed along three units (the first unit included 3 concepts, the second unit 7 concepts, and the third unit 8 concepts).